Manajemen Sumber Daya Manusia dalam Pendidikan Agama Kristen: Peran Guru dan Tenaga Kependidikan - Nofita Rudiani Asbanu; Hendrik A.E. Lao (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
Christian Religious Education (PAK) plays an important role in the formation of character and spirituality of students. This study aims to analyze human resource management (HR) in improving the effectiveness of the role of teachers and education personnel in the PAK environment. The approach used is a literature study, by analyzing literature, journals, and related references. The findings show that teachers are not only teachers, but also role models of Christian values. Continuous training, collaboration between teachers, cooperation with parents, and the availability of quality educational facilities are important factors in strengthening student character. A holistic management approach has been proven to be able to integrate cognitive, affective, and spiritual aspects. The implication is that adaptive and contextual HR management is needed so that PAK is able to answer the challenges of the times and form a generation with integrity.